2021
DOI: 10.3389/fspor.2021.699608
|View full text |Cite
|
Sign up to set email alerts
|

Brief Exercise at Work (BE@Work): A Mixed-Methods Pilot Trial of a Workplace High-Intensity Interval Training Intervention

Abstract: Introduction: The efficacy of high-intensity interval training (HIIT) for improving markers of physical fitness and cardiometabolic health is promising. The workplace is one non-laboratory setting where the effectiveness of HIIT could be explored. The aim of this study was to undertake a mixed-methods exploratory pilot trial of a workplace HIIT intervention named Brief Exercise at Work (BE@Work).Methods: Fifty-four healthy employees (mean ± standard deviation [SD] age 46 ± 10 years) from two workplaces in Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…Strategies to overcome these barriers include offering more opportunities to exercise throughout the workday and organising frequent group exercise classes [20]. Further, the variety of the exercise selection appears to be a key factor in facilitating exercise engagement, as a single exercise mode might not facilitate adherence or compliance [21]. In this context, time-efficient and enjoyable exercise modalities, such as high-intensity interval training (HIT) [22][23][24], could represent a strategy to overcome the perceived barriers to physical activity participation within the workplace [9].…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations
“…Strategies to overcome these barriers include offering more opportunities to exercise throughout the workday and organising frequent group exercise classes [20]. Further, the variety of the exercise selection appears to be a key factor in facilitating exercise engagement, as a single exercise mode might not facilitate adherence or compliance [21]. In this context, time-efficient and enjoyable exercise modalities, such as high-intensity interval training (HIT) [22][23][24], could represent a strategy to overcome the perceived barriers to physical activity participation within the workplace [9].…”
Section: Key Pointsmentioning
confidence: 99%
“…1). Of these, two studies were RCTs [38,39], one was a pilot RCT [40], and one was a mixed-methods pilot trial [21], while the remaining three were randomised [41] and non-randomised [42,43] feasibility studies. One study [39] reported the feasibility results in a separate subsequent paper [44].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, young people's experiences of taking part in HIIT remains unclear (Biddle and Batterham, 2015 ; Jung et al, 2015 ; Leahy et al, 2020 ; Weston et al, 2020 ). To date, only three detailed qualitative evaluations of real-world HIIT programmes exist, but these involved adult participants as part of a workplace intervention (Kinnafick et al, 2018 ; Metcalfe et al, 2020 ; Burn et al, 2021 ). Five school-based HIIT studies included aspects of process evaluation within their outcome trials (Buchan et al, 2013 ; Leahy et al, 2019 ; Kennedy et al, 2020 ; Lubans et al, 2020 ; Costigan et al, 2015b ).…”
Section: Introductionmentioning
confidence: 99%